The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1021/jo972045x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Fluorination of Enolates with Nonracemic N-Fluoro-2,10-Camphorsultams

Abstract: The asymmetric “electrophilic” fluorination of tertiary enolates by nonracemic N-fluoro-2,10-camphorsultams 3 affords quaternary α-fluoro carbonyl compounds in modest yield and ee. The highest asymmetric induction was observed for the fluorination of the sodium enolate of 2-methyl-1-tetralone (8a) by (−)-N-fluoro-2,10-(3,3-dichlorocamphorsultam) (3b) to give (S)-(+)-2-fluoro-2-methyl-1-tetralone (9a) in 70% ee. The absolute configuration was established by X-ray crystallography of the corresponding diastereome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(43 citation statements)
references
References 70 publications
(75 reference statements)
1
42
0
Order By: Relevance
“…We suggested rather that the axial orientations observed in their X-ray analyses could mainly result from either an intermolecular H-bond for 4a (NÀH ¥¥¥¥¥ OS) 6 ) or external forces such as solidÀsolid packing interactions for 4b [20]. We also refuted his argument by giving the example of the N-fluoro sultam 1c, which exists in both pseudo-axial/equatorial conformations, as shown by 19 F-NMR analyses [4], thus leading us to suggest a more modest anomeric stabilization, estimated as 1.5 kcal/mol [16]. Furthermore, based on DFT calculations with BeckeÀPerdew functionals and DN** polarization basis set [21], we also suggested that their rigidified six-membered-ring sultam 4b should, in solution, exist as Helvetica Chimica Acta ± Vol.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…We suggested rather that the axial orientations observed in their X-ray analyses could mainly result from either an intermolecular H-bond for 4a (NÀH ¥¥¥¥¥ OS) 6 ) or external forces such as solidÀsolid packing interactions for 4b [20]. We also refuted his argument by giving the example of the N-fluoro sultam 1c, which exists in both pseudo-axial/equatorial conformations, as shown by 19 F-NMR analyses [4], thus leading us to suggest a more modest anomeric stabilization, estimated as 1.5 kcal/mol [16]. Furthermore, based on DFT calculations with BeckeÀPerdew functionals and DN** polarization basis set [21], we also suggested that their rigidified six-membered-ring sultam 4b should, in solution, exist as Helvetica Chimica Acta ± Vol.…”
mentioning
confidence: 76%
“…Although reduced by the electronegativity of the halogen, the Nfluoro analogues 1c and 1d show the same stereoelectronic features. Noteworthy are the conformational energies of both thermodynamically more stable pseudo-equatorial N-fluoro sultams, in line with the values expected from their respective 19 F-NMR [4] [3] or X-ray 13 ) analyses. Due to the absence of a pseudo-equatorial SO functionality, the case of sulfinamide 2a is peculiar.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Controlling the α-stereochemistry through a carbon–carbon bond forming reaction could accomplish the equivalent of an asymmetric fluorination of a ketone, 47 a challenging transformation. Nakamura detailed the use of the tert -butyl PHOX ligand ( L-II ), while Tunge compared the PHOX ligand with another P,N-ligand, ( S )-QUINAP ( L-VI , Chart 9).…”
Section: Asymmetric Dca Of Enolatesmentioning
confidence: 99%
“…Very recently, Canadian authors, based on the X-ray analysis of a racemic six-membered-ring sultam, estimated the influence of the anomeric stabilization to 2.0 kcal/mol [26]. For the X-ray analysis of a N-fluorobornane-10,2-sultam, see [27].…”
mentioning
confidence: 99%